Pengujian Efek Kualitas Produk Halal dan Religiusitas Pada Loyalitas Konsumen Produk Wardah - Rafdhi Wira Oktavius Pelawi; Ariesya Aprillia (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The market for halal cosmetic products is very large, the majority of cosmetics and other maintenance products are produced by non-Muslim companies in several non-Muslim countries which can lead to an understanding regarding the halalness of various ingredients, due to concerns that many international brands use alcohol or enzymes extracted from pork as a preservative, the cosmetic and pharmaceutical industries have become the focus of research by Muslim scholars. This has led to a negative perception of this industry among Muslim consumers who are looking for Halal products. In a business full of competition, these negative perceptions must be minimized so that the company can survive, one way is to keep consumers loyal. The same circumstance is experienced by the company producing and marketing Wardah products. This study aims to examine the effect of halal product quality and religiosity on consumer loyalty to Wardah products in Bandung by setting the criteria in purposive sampling: the respondents have Islamic religion, buy Wardah products, and live in Bandung, 329 people are obtained as a sample. Moreover, the data obtained are verified for validity and reliability, and models by variance-based structural equation (SEM PLS). The estimation results of the structural equation model with the probability of the t-statistic are 0.001 for β1 = 0.253 and 0.000 for β2 = 0.542. Given that these two probabilities are less than α of 5%, the first and second research hypotheses are accepted. In conclusion, research shows that the quality of halal products and religiosity have a positive effect on consumer loyalty.